2021
DOI: 10.3389/fmolb.2021.691636
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Between Cell Cycle Progression and the Nuclear RNA Polymerases System

Abstract: Eukaryotic life is possible due to the multitude of complex and precise phenomena that take place in the cell. Essential processes like gene transcription, mRNA translation, cell growth, and proliferation, or membrane traffic, among many others, are strictly regulated to ensure functional success. Such systems or vital processes do not work and adjusts independently of each other. It is required to ensure coordination among them which requires communication, or crosstalk, between their different elements throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
(84 reference statements)
2
9
0
Order By: Relevance
“…16 Interestingly, it has been reported that RNA polymerase has the highest activity in the S-phase, which suggests a faster RNA synthesis rate and more G4 folding events. 42 Thus, we reasonably infer that cells may contain more RNA G4 in the S-phase. To test this hypothesis in our system, the Hela cells were treated separately to simulate the corresponding cell phase.…”
Section: ■ Introductionmentioning
confidence: 76%
“…16 Interestingly, it has been reported that RNA polymerase has the highest activity in the S-phase, which suggests a faster RNA synthesis rate and more G4 folding events. 42 Thus, we reasonably infer that cells may contain more RNA G4 in the S-phase. To test this hypothesis in our system, the Hela cells were treated separately to simulate the corresponding cell phase.…”
Section: ■ Introductionmentioning
confidence: 76%
“…A similar mechanism has been described in the alphaproteobacteria, where a circuit of antagonistic regulators act together to control transcription across the different phases of the cell cycle (reviewed Panis et al 2015). In eukaryotes, transcriptional control of the cell cycle is linked to the activity of cyclins and cyclin dependent kinases, which, among other changes, regulate the activity of the three RNA polymerases and are important for the G1/S transition (Delgado-Román and Muñoz-Centeno, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additional work is required to elucidate the role of RHH-domain transcriptional factors in regulating cell cycle progression in the Archaea domain.We predict the existence of several regulatory factors whose successive activation drives the transcription of different sets of genes during cell cycle progression. A similar mechanism has been described in the alphaproteobacteria, where a circuit of antagonistic regulators act together to control transcription across the different phases of the cell cycle (reviewedPanis et al 2015).In eukaryotes, transcriptional control of the cell cycle is linked to the activity of cyclins and cyclin dependent kinases, which, among other changes, regulate the activity of the three RNA polymerases and are important for the G1/S transition(Delgado-Román and Muñoz-Centeno, 2021).Regulation of cell growth, cytokinesis and DNA replication and segregation is exquisitely and robustly coupled in the three domains of life. These processes are linked together by several layers of regulation that involve different mechanisms and control strategies, and we envisage a similarly complex picture for the archaea domain.…”
mentioning
confidence: 82%
“…Progression through the cell cycle requires synthesis of more than 1000 cell cycle-dependent or cell cycle-related proteins [ 1 , 24 ]. This process is regulated at the transcriptional level primarily during the S and M phases.…”
Section: Control Of Transcription During the Cell Cyclementioning
confidence: 99%
“…This process is regulated at the transcriptional level primarily during the S and M phases. During the S phase, a group of genes encoding proteins important for DNA replication and DNA repair are transcribed, while another group of genes that encode proteins involved in mitosis and cytokinesis are expressed during the M phase [ 24 ]. Then, these cell cycle phase-specific proteins are subjected to proteasome-mediated degradation after completion of the S phase and the M phases, respectively, to ensure precisely ordered progression through the cell cycle and eventual exit from the cycle until mitotic cues are perceived to initiate another round of cell division.…”
Section: Control Of Transcription During the Cell Cyclementioning
confidence: 99%